(untitled) (Applied Biological Research, 2013)
Field studies were conducted to evaluate the efficacy of penoxsulam against complex weed flora both as pre- and post-emergence herbicide in transplanted rice during Kharif seasons of 2008 and 2009 at Mountain Research Centre for Field Crops, SKUAST-K, Khudwani, Kashmir (India) on a silty clay loam soil with normal reaction and medium fertility status. Major weed species infesting the field were Echinochloa crus-galli, Echinochloa colona, Cyperus iria., Cyperus difformis, Marsilea quadrifolia, Potamogeton distinctus, Ammania baccifera and Monochoria vaginalis. The experiment consisted of eight treatments replicated thrice and laid out in a randomized block design. Penoxsulum application @ 22.5 g a.i. ha-1as pre-emergence 3-5 days after transplantation (DAT) provided effective control of almost all types of weed species thereby resulting in higher paddy yield (72.8 q ha-1) as compared to weed-free (77.2 q ha-1) and two hand weeding (71.9 q ha-1). Penoxsulam @ 20 g ai ha-1 was also effective in controlling weeds when applied as post-emergence (8-12 DAT) and gave a paddy yield of 69.2 q ha-1.